The Effect of a workshop on "instructional design" on the capability and attitudes of faculty members of the College of Pharmacy and Medical Technology (CPMT), MCU - Valdez, Teresa D.
The study investigates whether there is a significant change in the capability of faculty members who have undergone a workshop. Its purpose is to look into the effect of a workshop on the capability and attitude of faculty members in designing their course of instruction which includes the essential elements: the objectives, learning activities, resources and evaluation. The study group were the faculty members of CPMT, MCU who have little or no formal training in teaching. A pre-test based on the concept of instructional design was given to all participants. Two weeks after, the workshop was conducted for four staggered days. Each session of the workshop consisted of a mini-lecture, a workshop on the application of the workshop outputs. The posttest was given on the final day of the workshop. The results of the pre and post tests were analyzed using the paired scores t-test setting the level of significance at p < .05. The test items were analyzed using the Chi-square set at a level of p<.05 with one degree of freedom. Workshop outputs were evaluated using a checklist covering five areas: the instructional situation, objectives, learning activities/resources, visual aids and evaluation. To assess the effect of workshop on the attitudes of faculty members toward teachers' training workshop, a rating scale was used. Effectivity of the workshop as a training program revealed a marked improvement of the educational knowledge of faculty members. The computed t-value was 10.246 compared to the tabular t-value of 1.771. Of the total test items, 67.24% indicated desirable improvement of the cognitive knowledge of the participants. Portions in teachers' activities requiring workshop follow-up were in evaluation and uses of reference systems in grading. Eighty percent (80%) of the participants favorably met the criteria set for the workshop outputs. An average response of 4.5 on a 5-point rating scale showed a highly favored effect of the workshop on the attitude of faculty members. The overall results proved that the workshop can produce a significant change on the capability and attitudes of faculty members.